(untitled) - Roberts, Paul (Boston, 2004)
A non-fiction, it provides an analysis of the various problems associated with humanity's reliance on oil and other fossil fuels such as coal and natural gas.
Keywords: Công nghiệp dầu khí và thương mại,Petroleum industry and trade; Chính sách của chính phủ,Government policy; United States